Management of the Independent Curriculum Towards Effective Learning in Senior High Schools of South Aceh Regency - Eva Julita; Niswanto (International Journal of Educational and Life Sciences, 2025)
The Merdeka Curriculum, introduced by the government, has been implemented in various regions, including South Aceh Regency, aiming to provide schools with flexibility in designing learning processes suited to students' needs and potential. The management of the Merdeka Curriculum involves organizing and overseeing its implementation in schools. This study aims to explore: (1) the planning of the Merdeka Curriculum for effective learning in high schools in South Aceh; (2) its implementation; (3) the evaluation process; and (4) follow-up actions to ensure effective learning. Using a qualitative approach, the research focuses on SMA Negeri 1 Labuhan Haji Timur, SMA Negeri 1 Samadua, and SMA Negeri 1 Kluet Selatan. Data collection methods include observation, interviews, and document analysis, while data analysis involves collection, reduction, presentation, and conclusion drawing. Key findings include: (1) Planning begins with the work plans of school leadership teams. (2) The Merdeka Curriculum has been implemented for two years and is currently at level 2, "Merdeka Berubah." (3) Evaluation is conducted through input, process, output, and outcome analysis. (4) Follow-up actions include identifying challenges, teacher training, provision of learning facilities, scheduled supervision, and effective communication. Proper management of the Merdeka Curriculum is expected to optimize its implementation, ensuring effective learning.